The role of HbA1c in the bidirectional relationship between periodontitis and diabetes and related interventions: a narrative review - Yudie Du; Yudie Du; He Xiao; He Xiao; Ruihan Luo; Ruihan Luo; Guangyi Li; Guangyi Li; Yixing Ren; Yixing Ren; Yixing Ren (Frontiers in Nutrition)
ObjectiveThe intricate relationship between periodontitis and diabetes mellitus (DM) has emerged as a focal point in contemporary medical research. This study aimed to explore the role of glycated hemoglobin (HbA1c) in this relationship, examine the mechanistic theories that may underlie this connection, and summarize effective interventions.MethodsArticles were retrieved from PubMed/Medline and Web of Science. All studies focusing on this bidirectional relationship were included and evaluated.ResultsSeveral mechanism theories have been proposed, including alterations in oral flora, suppression of anti-inflammatory and antidiabetic control mechanisms in periodontitis, gene silencing due to reduced DNA demethylation, and significantly lower quantitative levels of platelet-rich fibrin (PRF). Non-surgical periodontal therapy (NSPT) is an effective intervention, and based on this, systemic antibiotics and propolis can also be used. Antimicrobial photodynamic therapy (aPDT) is also an adjunct to periodontal therapy, with indocyanine green currently receiving increased attention.DiscussionHbA1c links periodontitis and DM bidirectionally, with elevated levels contributing to the worsening of periodontal disease and tooth loss. Studies have confirmed this association in both diabetic and non-diabetic individuals, although some findings remain conflicting. While HbA1c may predict diabetes risk and periodontal severity, further research is needed to clarify this relationship.ConclusionThere is a bidirectional relationship between periodontitis and DM, with HbA1c playing an important role in this relationship. However, this study has certain limitations regarding selection bias and methodology, necessitating further mechanistic exploration and clinical validation in subsequent research.